You are at rock bottom: A qualitative systematic review of the needs of bereaved parents as they journey through the death of their child to cancer. Issue 6 (1st November 2020) - Kenny, Méabh; Darcy-Bewick, Sinead; Martin, Aoife; Eustace-Cook, Jessica; Hilliard, Carol; Clinton, Frieda; Storey, Lorna; Coyne, Imelda; Murray, Kim; Duffy, Katie; Fortune, Gillian; Smith, Owen; et al.
Abstract: Problem Identification: This systematic review will examine the social support needs of bereaved parents in the specific context of pediatric cancer by synthesizing the qualitative evidence. Social support encompasses emotional, practical, informational, and meaning-making support needs. Literature Search: The Joanna Briggs Institute procedures for conducting qualitative systematic reviews guided every stage of this review. Four databases (PsychInfo, CINAHL, Pubmed, and ASSIA) were systematically searched, in addition to the gray literature and scoping review. Through a five-step critical appraisal process 11 out of 668 potential articles were identified as meeting the inclusion criteria. Data Evaluation/Synthesis: Relevant findings were synthesized with a thematic-synthesis approach. Findings, which follow the journey of bereaved parents integrated under the core-category "Needs." This encompasses of four higher-level categories: Last days: Parent needs when caring for their dying child Rest in peace: Parent needs during the child's death Feeling abandoned: Parent needs for contact after the child's death Searching for Meaning: Parents needs when making sense of loss Conclusion: Informational support needs is largely unexplored in academic literature. Staff in the treating-hospital are central in offering bereavement-support to parents, who may otherwise feel that they have lost their second home (hospital) and second family (staff).